Os Cristos da Paixão da Ordem Terceira do Carmo de Ouro Preto (MG) - Lia Sipaúba Proença de Moraes (2014)
In Brazil colony, during century XVIII and beginning of the XIX, in the Capitania of Minas, the Christian religion was perpetuated by its devotinals images. Colonial sacraded imaginary composes a field of ample and interdisciplinary study. This work has as objective to analyze the iconographic representations, the techniques and materials of the sculptures of Christs Passion, located in the sides retables of the nave and retables of the consistory of the Church of the Third Order of Ours Lady of Carmel of Ouro Preto (MG). This research emphasis the technology of the sculpture in wood with lead mask polychomatedes, known as mascarilla. The methodology applied for this study is based on a bibliographical survey in the areas of history, art and iconography to embrace a documentary research. The research in loco is based in photographic register, inquiry of materials, techniques and scientific analyses of the Christs of the Passion. Such sculptures present a constructive technology in variations of Images To Dress and Whole Carvings. Its technique of the mask in polychomated lead mold was common in Spain and Andean countries, is rare in Minas Gerais. These images must be preserved and recognized as important source of historical, artistic and social research.